2015
DOI: 10.1016/s0924-9338(15)31245-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Efficacy of Bupropion and Amantadine On Sexual Dysfunction Induced by a Selective Serotonin Reuptake Inhibitor

Abstract: Background: Antidepressant-induced sexual dysfunction (SD) is a common problem, associated with a significant risk of non-adherence. Selective Serotonin Reuptake Inhibitors (SSRIs) are associated with a substantial risk of SD. Only 10 % of patients show spontaneous improvement during follow up period. Objectives: This study aimed to compare two proposed medication (bupropion vs. amantadine) in alleviating SD in patients treated with SSRIs. Patients and Methods:In a randomized, single-blinded, clinical trial in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…28 In this blinded trial of bupropion (200 mg/day) versus amantadine (200 mg/day), the bupropion group reported more improvement in desire, arousal, and pleasure. A doubleblind, randomized, placebo-controlled study that was published in favor of bupropion augmentation was later retracted.…”
Section: Switch To or Add Bupropionmentioning
confidence: 93%
“…28 In this blinded trial of bupropion (200 mg/day) versus amantadine (200 mg/day), the bupropion group reported more improvement in desire, arousal, and pleasure. A doubleblind, randomized, placebo-controlled study that was published in favor of bupropion augmentation was later retracted.…”
Section: Switch To or Add Bupropionmentioning
confidence: 93%